Gambaran Faktor Risiko yang Menyebabkan Terjadinya Perdarahan Post Partum pada Ibu Bersalin di RSUD Pare Kediri - Fitri Yuniarti (STIKES Karya Husada Kediri, 2018)
Hemorrhage post partum is bleeding 500 cc or more after the third stage is complete or after the placenta is born. The incidence of post partum hemorrhage increases due to several risk factors, namely: maternal age, parity, birth distance, labor history, anemia, long and gemelli delivery. This study is sequential to determine the risk factors that cause post partum hemorrhage at the Pare Kediri Regional General Hospital.The research design used in this study was descriptive by using a single variable, namely the risk factor for the cause of post partum hemorrhage at the Pare Kediri Regional General Hospital. The sample size of 29 respondents was post partum mothers who had bleeding with complete medical record data from January 2015 to May 2015. The sampling technique used total sampling (saturated sampling). The study was conducted on 5 September-5 October 2015 with 29 respondents. Secondary data collection by looking at medical records. Data analysis with descriptive statistics. Based on the results of the study it can be described that most post partum hemorrhages are caused by anemia as much as 69%, long parturition 59% and a small part due to maternal age as much as 31%, history with comorbidities as much as 17%, birth distance 17%, history of sectio caesarea 7% and grand culture of 7%. The cause of bleeding in Kediri Pare Hospital is mostly caused by anemia and prolonged labor and a small part is caused by the age of the mother, history of labor, distance of birth and grandemultipara. Anemia and prolonged labor are the causes of bleeding, especially in post partum mothers because prolonged labor tends to occur in uterine atony which causes bleeding.